The Importance of the Training System of Guide Translators in using the Tourist Authority of Samarkand Region (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, guides play an important role in promoting the richness of historical and cultural heritage, in awakening tourists' great interest in our material and cultural heritage, and in increasing the promotion of tourism services.